EFFECT OF SPRAYING BA AND ZN AT VEGETATIVE AND ROOT SYSTEM GROWTH OF PLUM SAPLINGS - A. Y. Salih; A. Q. Hamdan; S. M. Tarkan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate effects of Benzyl Adenine and Zinc sulfate on Plum trees growth, at the field of Depart. Horticultural and Landscape, College of Agricultural Engineering Sciences, University of Baghdad, during the spring season of 2021. Spraying three different concentrations (0, 50, and 100) mg.L-1 of Benzyl adenine and foliar applications of Zinc sulfate with three different concentrations (0, 25, and 50) mg.L-1 on vegetative and root system traits, as well as the chemical content of Plum seedlings (Prunus domestica L.) grafted on to Apricot rootstocks. The experiment conducted using factorial experiment with a Randomized Complete Block Design and, three replicates, Two seedlings per treatment, were used. The results revealed significant differences concerning the foliar application of Benzyl Adenine, particularly at the 100 mg/L concentration. which had a substantial impact on various vegetative traits. Additionally, it exhibited a superior effect on root characteristics.. Conversely, Zinc element demonstrated significant superiority at the concentration of 50 mg/L concerning the same vegetative and root traits,.